A MicroRNA-Based Network Provides Potential Predictive Signatures and Reveals the Crucial Role of PI3K/AKT Signaling for Hepatic Lineage Maturation - Wang, Xicheng; Zhang, Wencheng; Yang, Yong; Wang, Jiansong; Qiu, Hua; Liao, Lijun; Oikawa, Tsunekazu; Wauthier, Eliane; Sethupathy, Praveen; Reid, Lola M.; Liu, Zhongmin; He, Zhiying (Frontiers in Cell and Developmental Biology, 2021)
Available soon